Personality Traits and Psychotic Proneness Among Chronic Synthetic Cannabinoid Users - Cohen, Koby; Rosenzweig, Shiri; Rosca, Paola; Pinhasov, Albert; Weizman, Abraham; Weinstein, Aviv (Frontiers in Psychiatry, 2020)
Objective: Chronic use of synthetic cannabinoids (SCs) has been associated with a wide range of negative consequences for health including psychotic and affective disturbances. Accumulating evidence indicates that cannabinoids use may be a risk factor for schizophrenia, and chronic natural cannabis users score higher than non-users on measures of schizotypal personality traits. However, little is known regarding the personality characteristics of SC users, especially in comparison with recreational cannabis users and healthy individuals. This study aimed to examine the differences in personality characteristics and schizotypy between SC users, regular cannabis users and non-users and to compare these measures between groups. Methods: 42 chronic SC users, 39 natural cannabis users, and 47 non-using control participants , without history of mental disorder, or current substance use diagnosis (mean age 26 4.47 years; 23 females, 105 males), completed the Big-Five Factor Inventory (BFI), the Schizotypal Personality Questionnaire-Brief (SPQ-B), substance use history, rating scales of depression and anxiety and a demographic questionnaire. Results: On the BFI, SC users scored higher than natural cannabis users and non-users on neuroticism, but lower on agreeableness and extraversion, and endorsed greater schizotypal symptoms on the SPQ-B. In addition, SC users had lower scores on conscientiousness than non-users, and natural cannabis users were more extroverted than non-users. Higher openness and lower conscientiousness predicted schizotypy for both SC and natural cannabis users. Finally, greater neuroticism predicted schizotypy for natural cannabis users, and introversion predicted schizotypy for non-users. Conclusions: These results show that chronic SC users differ from natural cannabis users and non-users on dimensions of specific personality traits and schizotypy that may indicate psychotic proneness.